THE EFFECT OF LEARNING MOTIVATION AND PARENTS’ ROLE ON THE ACHIEVEMENT INDEX IN PGMI STUDENTS' ONLINE LEARNING - Yulia Pramusinta; Silviana Nur Faizah (Auladuna: Jurnal Pendidikan Dasar Islam, 2022)
Abstract COVID-19 became a problem in Indonesia, especially in education. The whole educational level ranging from basic to higher education is required to learn from home or online. This study aimed to find: (1) the learning motivation effect on the Achievement Index (AI), (2) the parents’role effect on AI, and (3) the interaction of learning motivation and parents’ role in AI. This research used a descriptive quantitative method with a google form survey approach. The sample in this study was 154 students of PGMI study program for the even semester in 2020/2021. The analysis technique used was multiple linear regression analysis to test three hypotheses. The results showed that: (1) there was an influence of learning motivation on students' AI, (2) there was an influence of parents' role on AI, and (3) there was an interaction between learning motivation and parents' role in students' AI.